2021
DOI: 10.3390/molecules26041071
|View full text |Cite
|
Sign up to set email alerts
|

Loganin Alleviates Gout Inflammation by Suppressing NLRP3 Inflammasome Activation and Mitochondrial Damage

Abstract: Gout is a type of inflammatory arthritis caused by the deposition of monosodium uric acid (MSU) crystals in tissues. The etiology of gout is directly linked to the NLRP3 inflammasome, since MSU crystals are NLRP3 inflammasome activators. Therefore, we decided to search for a small-molecule inhibitor of the NLRP3 inflammasome for the prevention of gout inflammation. We found that loganin suppressed MSU crystals-induced caspase-1 (p20) and interleukin (IL)-1β production and apoptosis-associated speck-like protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 29 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…58 , 59 Therefore, directly targeting NLRP3 and its associated factors or proteins may effectively inhibit NLRP3 activation and potentially produce benefits in gout treatment. 60 Previous clinical trials utilizing different drugs that target only a single step in a specific disorder have failed. However, in this study, carvacrol ameliorated the detrimental effects of hyperuricemia by targeting multiple stages, including inflammation, oxidative stress, and cellular degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…58 , 59 Therefore, directly targeting NLRP3 and its associated factors or proteins may effectively inhibit NLRP3 activation and potentially produce benefits in gout treatment. 60 Previous clinical trials utilizing different drugs that target only a single step in a specific disorder have failed. However, in this study, carvacrol ameliorated the detrimental effects of hyperuricemia by targeting multiple stages, including inflammation, oxidative stress, and cellular degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, neoastilbin inhibited GA, including inflammatory cytokine release and inflammatory cell infiltration into the lesion site, mediated by the suppression of NF-κB and NLRP3 inflammasome pathways in THP-1-derived macrophages and GA mice. Considering that the NF-κB and NLRP3 inflammasome pathways are related to the development of many inflammatory diseases, neoastilbin may have potential clinical application value in gout, autoinflammatory syndrome or other NLRP3-driven diseases [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammasomes can promote the cleavage of pro‐IL‐1β and pro‐IL‐18 into mature IL‐1β and IL‐18, which in turn induces the death of inflammatory cells. It has been shown that loganin can reduce gouty arthritis by inhibiting the activation of NLRP3 inflammasomes and mitochondrial dysfunction (Choi et al, 2021).…”
Section: Pharmacology Of Loganinmentioning
confidence: 99%